Japan's Financial Crisis : Institutional Rigidity and Reluctant Change - Amyx, Jennifer Ann (Book collections on Project MUSE., 2004)
At the beginning of the 1990s, a massive speculative asset bubble burst in Japan, leaving the nation's banks with an enormous burden of nonperforming loans. Banking crises have become increasingly common across the globe, but what was distinctive about the Japanese case was the unusually long delay before the government intervened to aggressively address the bad debt problem. The postponed response by Japanese authorities to the nation's banking crisis has had enormous political and economic consequences for Japan as well as for the rest of the world. This book helps us understand the natur.